A dark foe [videorecording (DVD)] - Cardenas, Maria Gabriela; Cardenas, Oscar (Actor); Cardenas, Oscar (Actor); Dalton, Kenzie; Black Elk, Tokala; Morshower, Glenn, 1959-; Lindstrom, Jon, 1957- (Vertical Entertainment, 2021)
A guilt-ridden FBI agent, stranded in the painful memory of the abduction of his sister, will have to face-off with the cunning serial killer who took her away.